Sonic psychogeography: A poetics of place in popular music in Aotearoa/New Zealand - Mitchell, Tony (Perfect Beat, 2009)
This article explores aspects of the relationship between music, place, locality and identity in Aotearoa/New Zealand. While there have been numerous attempts to construct a national identity for New Zealand music (often referred to as ‘Kiwi’ music), I will argue that there is far more comprehensive evidence of a range of regional musics, which go beyond examples such as the Flying Nun-Dunedin Christchurch and roots-reggae-dub-Wellington nexus, and suggest rather a local-transnational nexus, which combines strong global influences with evocations of particular localities. This transnational orientation suggests a liminal or ‘in-between’ situatedness for much music produced in New Zealand, in which landscape and ‘sonic geography’, whether urban or rural, is not related to expressions of national identity, but to a more locally- grounded poetics of home, belonging, and also alienation. In exploring ‘psychogeographical’ aspects of a range of popular music in Aotearoa, I will examine remixes of taonga puoro music (pre-European Maori musical instruments) by Richard Nunns and Hirini Melbourne by various dub and electronica musicians, music by Neil Finn, Don McGlashan, Bachelorette, Roy Montgomery, and music inspired by places in the South island, especially the ‘landscape of trauma’ of the Aramoana massacre of 1990.